Mapping the impact of the expanded Mexico City Policy for HIV/ family planning service integration in PEPFAR-supported countries: a risk index - Jennifer Sherwood; Alana Sharp; Brian Honermann; Caitlin Horrigan; Meghna Chatterjee; Austin Jones; Chloe Cooney; Greg Millett (BMC, 2018)
Abstract Background The previously-named Mexico City Policy (MCP) - which prohibited non U.S.-based non-governmental organizations (NGOs) from receiving U.S. family planning (FP) funding if they advocated, provided, counseled, or referred clients for abortions, even with non-U.S. funds - was reinstated and expanded in 2017. For the first time, the expanded MCP (EMCP) applies to HIV funding through the President's Emergency Plan for AIDS Relief (PEPFAR) in addition to FP funding. Previous, and more limited, iterations of the policy forced clinic closures and decreased contraceptive access, prompting the need to examine where and how the EMCP may impact FP/HIV service integration. Methods The likelihood of FP/HIV service de-integration under the EMCP was quantified using a composite risk index for 31 PEPFAR-funded countries. The index combines six standardized indicators from publically available sources organized into three sub-indexes: 1) The importance of PEPFAR for in-country service delivery of HIV and FP services; 2) The susceptibility of implementing partners to the EMCP; and 3) The integration of FP/HIV funds and programming through PEPFAR and USAID. Results Countries with the highest overall risk scores included Zambia (3.3) Cambodia (3.2), Uganda (3.1), South Africa (2.9), Haiti (2.8), Lesotho (2.8), Swaziland (2.1), and Burundi (1.5). Zambia's risk score is driven by sub-index 1, having a high proportion of country HIV expenditures provided by PEPFAR (86.3%). Cambodia and Uganda's scores are driven sub-index 3, with both countries reporting 100% of PEPFAR supported HIV delivery sites were providing integrated FP services in 2017. South Africa's risk score is driven by sub-index 2, where roughly 60% of PEPFAR funding is to non U.S.-based NGOs. Of the countries with the highest risk scores, Swaziland, Lesotho, and South Africa, are also in the top quartile of PEPFAR countries for HIV prevalence and unintended pregnancies among young women. Conclusion This analysis highlights where and why the EMCP may have the greatest impact on FP/HIV service integration. The possible disruption of service integration in countries with generalized HIV epidemics highlights significant risks. Researchers, national governments, and non-U.S. funders can consider these risk factors to help target their responses to the EMCP and mitigate potential harms of the policy.